COGNITIVE PERCEPTION IN SUPERVISION - Рубанець, О. (SWorldJournal, 2025)
The article considers methodological aspects of the use of cognitive technologies. The need to expand the scope of application of cognitive technologies is substantiated. The task of using cognitive technologies for resocialization, social adaptation and